The conditions for intercultural dialogue according to Raúl Fornet-Betancourt - TUBINO, Fidel (Utopía y Praxis Latinoamericana, 2022)
The author explores, based on Raúl Fornet-Betancourt's book: Interculturality on Trial, what are the conditions for intercultural dialogue to take place. It is based on a deep knowledge about the author of reference, highlighting and considering spiritualities, incarnated knowledge, intersubjectivity and, of course, dialogue. It reaffirms the proposal of intercultural dialogue, emphasizing the different contexts in which these encounters between different knowledge take place, and in this way, the proposal is put into practice.